Effects of electron-phonon interactions on the spin-dependent Seebeck effect in graphene nanoribbons. (August 2017) - Li, Bo-Lin; Chen, Ke-Qiu
Abstract: Based on the nonequilibrium Green's function and density functional theory, a method to investigate the spin-dependent Seebeck effect (SDSE) with consideration of inelastic transport processes is presented. Results show that phonons with lower vibration energy may have more possibilities to contribute thermal drive inelastic currents and affect the SDSE properties. Consideration of inelastic processes may show both promotive or restrictive corrections to the SDSE properties. A sample calculation in graphene nanoribbons shows that the inelastic processes may contribute approximately two times the elastic current and will promote the SDSE of this sample device. We see that the main source of the large inelastic currents is coupling to the in-plane breathing mode. These results may be helpful for understanding of the physical process underlying the SDSE. Graphical abstract: